Revisiting calendar effects in Malaysian finance stocks market: Evidence from threshold GARCH (TGARCH) model - Qaiser Munir; Kok, Sook ching (2019)
Recent research reveals that calendar effects have largely disappeared from stock markets. However, majority of the past studies focus on stock markets at the aggregate level but do not provide firm-level evidence. Therefore, this study investigates day-of-the-week and month-of-the-year effects in Malaysian finance stocks market for the period 1/1/1997–31/12/2014. The empirical results from threshold GARCH (TGARCH) model suggest that certain daily and monthly seasonality effects are prevalent along with asymmetric news effect. The findings of study indicate inefficiency in the weak-form sense, implying that it is possible for investors to obtain the observed abnormal returns by using timing strategies.